Autumn Exhibition 2001. (London : Marlborough Fine Art Ltd., 2001)
Abakanowicz, Magdalena ; Arikha, Avigdor ; Auerbach, Frank ; Bramham, Christopher ; Brun, Christopher Le ; Campbell, Steven ; Chen Yifei ; Conroy, Stephen ; Davies, John ; Hubbard, John ; Jacklin, Bill ; Kiff, Ken ; Kitaj, R.B. ; Mason, Raymond ; Oulton, Thérèse ; Pasmore, Victor ; Paul, Celia ; Rego, Paula ; Willing, Victor
biog., coll. per kunstenaar
Autumn Exhibition 2001, Marlborough Fine Art Ltd., London, 7 - 29 September 2001
Engels
boek